Effects of nano-selenium and/or vitamin E supplementation on growth performance, antioxidant status, histopathology and resistance to Aspergillus flavus in Nile tilapia (Oreochromis niloticus) - Walaa K. Bazina; Wesam A. Tawfik; Nadia A. Abd Elghany; Saadea Saadony; Zulhisyam Abdul Kari; Muna Omer Alamoudi; Mohamed Y. M. Aly; Abuelhassan Elshazly Younis; Roshmon Thomas Mathew; Moaheda E. H. Eissa; Mohammad Bodrul Munir; Saadiah Ibrahim; et al. (BMC Veterinary Research)
Abstract Background This study aimed to evaluate the effects of selenium nanoparticles (SeNPs) and/or vitamin E (VE) on the growth, body composition, metabolic parameters, histopathology, and resistance of Nile tilapia to Aspergillus flavus. Results Monosex Nile tilapia fingerlings were sourced from the Bazina farm and hatchery in Ismailia Governorate, Egypt, where the experiment was also conducted. The fish were acclimatized for 15 days before the trial. A total of 240 fingerlings (average weight 46 ± 3.0 g/fish) were divided equally across 12 concrete tanks (1 × 1 × 1.2 m, 1 m³ capacity), with 20 fish per tank. The fish were fed a control diet (T0), which was a basal diet with no supplementation, or one of three experimental diets for 60 days: T1 (1 mg SeNPs/kg), T2 (100 mg VE/kg), and T3 (1 mg SeNPs + 100 mg VE/kg). The experiment followed a completely randomized design (CRD) with three replicates per treatment. The combination of SeNPs and VE (T3) resulted in the best feed conversion ratio. A slight but significant increase (P  < 0.05) in whole-body composition was observed in all treatment groups compared to the control. Biochemical parameters, serum digestive enzyme activity, and antioxidant levels improved significantly with dietary supplementation. Histopathological analysis revealed somewhat lacerated gill arches in fish fed SeNPs, VE, or their combination, but the overall gill structure remained normal. The SeNPs + VE group exhibited improved villi length and normal morphology of portal veins and hepatic sinusoids, though some vacuolated hepatocytes were noted. Fish in the SeNPs + VE group had the lowest mortality rates and the highest resistance to A. flavus. Conclusion Supplementing diets with SeNPs and/or VE enhances growth, body composition, biochemical parameters, and histopathology in Nile tilapia. The combination of 1 mg SeNPs + 100 mg VE/kg improves immune response and growth, offering a promising strategy to enhance Tilapia health and productivity.